Implementasi Kebijakan COVID-19 di Pondok Pesantren: Studi Kasus Pondok Pesantren Jamil Kecamatan Kesugihan, Kabupaten Cilacap - Elita Hermawanti; Fadly Husain (Universitas Hamzanwadi, 2023)
The implementation of the COVID-19 policy is the result of adjusting the existing conditions within the Islamic boarding school environment. With the implementation of the COVID-19 policy causing a social rearrangement included in the world of education. The purpose of this study is to understand the implementation of the COVID-19 policy in the Jamil Islamic Boarding School environment and identify the responses shown by Jamil Islamic Boarding School residents to the implementation of the policy. This research uses qualitative methods of the case study type that produce descriptive data. The results of the research show that the Kiai are the most important decision-makers. The determinants of the application of implementation are based on the conditions of Islamic boarding schools in the fields of education and health which are divided into two policies namely zhohir (physical) and bathiniyah (inner). This raises various responses from residents of Islamic boarding schools, especially students. These responses fall into five aspects, namely health recommendations, attitudes toward the government, stigma, religion, and personal identity. Implementation of policies through approaches through religion and respected religious leaders is more acceptable to Islamic boarding school residents compared to policies issued only by the government.